Спеціальні, автономні, самодостатні, функціональні та цільові режими в міжнародному праві - Поєдинок, О.Р. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Исследуются проблемы появления и развития специальных, автономных, самодостаточных, функциональных и целевых режимов в международном праве. Анализируются вопросы терминологии, возможности существования таких режимов и степени их зависимости от остальных норм международного права, а также их значения для будущего международного права. The article deals with the problem of the emergence and the development of special, autonomous, self-contained, functional, and objective regimes in international law. Specifically, the issues of terminology, the possibility of such regimes' existence as well as the degree of their dependence on the rest of international law and their importance for the future of international law were investigated.